Law in the era of new technologies: trends and development prospects - Shakhray, Irina S.; Kuzmich, Iryna P. (Journal of the Belarusian State University. Law, 2022)
The article analyses the trends and prospects for the development of law as a social institution at the present stage of technological development, which is characterised by the comprehensive nature of the new technologies penetration into all spheres of the functioning of society and the state. It is concluded that the transformation of legal reality under the influence of new technologies manifests itself in various forms (from the emergence of separate legal norms and legal institutions of the same industry to the law transformation as a whole, its system, forms, content), and the process of mutual influence of new technologies and law is cyclical. The key problems which characterise the modern Belarusian legislation in the light of the spread of new technologies are noted, and the need to develop an interdisciplinary approach to overcome them, taking into account the fundamentally new nature of the objects about which social relations are formed.
Keywords: new technologies; law; legal regulation; transformation